OS CONCEITOS DE CONSCIÊNCIA HISTÓRICA E OS DESAFIOS DA DIDÁTICA DA HISTÓRIA (Revista de História Regional, 2007)
The historical consciousness' concept appears in several authors and tendencies of the Human Sciencies. The purpouse of this text is to confrontate such authors, mainly Agnes Heller and Jörn Rüsen, and acess the importance of these debates to the history teaching or history didactics. This importance lies basically at the increase of research fields of this borderline area between educationand history.